Pigmented Variant of Dermatofibrosarcoma Protuberans (Bednar Tumor) Masquerading as Vascular Lesion on Imaging - Kalaivanan Balasubramanian; Paruvathavarthini Thambiraj; Bheemanathi Hanuman Srinivas (International Journal of Advanced Medical and Health Research, 2025)
A pigmented variant of dermatofibrosarcoma protuberans (DFSP) is a rare variant with intermediate-grade potential and has the propensity for local recurrence. It is essential to understand the morphology of this tumor, and it needs to be differentiated from other pigmented lesions of the skin. It is unusual for this tumor to present as a vascular lesion on radiological investigation. Here, we report the case of a 38-year-old male with a thigh mass and imaging features suggestive of vascular malformation. He was diagnosed with a pigmented variant of dermatofibrosarcoma protuberans following histopathology of the excision biopsy specimen. We report this case due to the rarity of the entity and its masquerading as a vascular lesion on imaging.